2021
DOI: 10.1016/j.techsoc.2021.101780
|View full text |Cite
|
Sign up to set email alerts
|

Applied Artificial Intelligence and user satisfaction: Smartwatch usage for healthcare in Bangladesh during COVID-19

Abstract: The evolution of Artificial Intelligence (AI) has revolutionized many aspects of human life, including healthcare. Amidst the Covid-19 pandemic, AI-enabled smartwatches are being used to help users to self-monitor and self-manage their health. Using a framework based on Stimulus-Organism-Response (S–O-R) theory, this present study aimed to explore the use of AI-enabled smartwatches for health purposes, in particular the effects of product quality, service quality, perceived convenience, and perceived ease of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 169 publications
3
33
0
Order By: Relevance
“…Hsu et al (2015) and Khatoon et al (2020) mentioned the effects of perceived playfulness. They perceived flow on customer satisfaction and purchase intentions using playfulness and perceived flow as an outcome (Uzir et al, 2021a). The findings revealed that the customer's perception of playfulness and flow is influenced by the quality of the website (Amin et al, 2020;Ashfaq et al, 2020).…”
Section: The Relation Of Customer Satisfaction Of Online Purchasing W...mentioning
confidence: 95%
See 4 more Smart Citations
“…Hsu et al (2015) and Khatoon et al (2020) mentioned the effects of perceived playfulness. They perceived flow on customer satisfaction and purchase intentions using playfulness and perceived flow as an outcome (Uzir et al, 2021a). The findings revealed that the customer's perception of playfulness and flow is influenced by the quality of the website (Amin et al, 2020;Ashfaq et al, 2020).…”
Section: The Relation Of Customer Satisfaction Of Online Purchasing W...mentioning
confidence: 95%
“…Accordingly, it was adapted and added as a construct into the established technology adoption model (Venkatesh et al, 2012). Thus, value in the shopping process raises the pleasure and emotional involvement provided by the bargaining process (Uzir et al, 2021a;Hassan et al, 2022;Naveed et al, 2022). According to Venkatesh et al (2012), the pleasure and satisfaction generated by the bargaining process is a kind of hedonic shopping value.…”
Section: The Relation Of Hedonic Motivation With Customer Satisfactio...mentioning
confidence: 99%
See 3 more Smart Citations